Controversies about Interspinous Process Devices in the Treatment of Degenerative Lumbar Spine Diseases: Past, Present, and Future. (13th April 2014) - Gazzeri, Roberto; Galarza, Marcelo; Alfieri, Alex
Abstract : A large number of interspinous process devices (IPD) have been recently introduced to the lumbar spine market as an alternative to conventional decompressive surgery in managing symptomatic lumbar spinal pathology, especially in the older population. Despite the fact that they are composed of a wide range of different materials including titanium, polyetheretherketone, and elastomeric compounds, the aim of these devices is to unload spine, restoring foraminal height, and stabilize the spine by distracting the spinous processes. Although the initial reports represented the IPD as a safe, effective, and minimally invasive surgical alternative for relief of neurological symptoms in patients with low back degenerative diseases, recent studies have demonstrated less impressive clinical results and higher rate of failure than initially reported. The purpose of this paper is to provide a comprehensive overview on interspinous implants, their mechanisms of action, safety, cost, and effectiveness in the treatment of lumbar stenosis and degenerative disc diseases.